2014
DOI: 10.1371/journal.pone.0092974
|View full text |Cite
|
Sign up to set email alerts
|

Low Doses of Gamma-Irradiation Induce an Early Bystander Effect in Zebrafish Cells Which Is Sufficient to Radioprotect Cells

Abstract: The term “bystander effect” is used to describe an effect in which cells that have not been exposed to radiation are affected by irradiated cells though various intracellular signaling mechanisms. In this study we analyzed the kinetics and mechanisms of bystander effect and radioadaptation in embryonic zebrafish cells (ZF4) exposed to chronic low dose of gamma rays. ZF4 cells were irradiated for 4 hours with total doses of gamma irradiation ranging from 0.01–0.1 Gy. In two experimental conditions, the transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 51 publications
0
29
2
Order By: Relevance
“…Recently, Pereira et al showed that γ irradiation increased the global methylation in both irradiated and bystander embryonic zebrafish fibroblast (ZF4) cells through mass spectrometry analyses [223]. High performance liquid chromatography–tandem mass spectrometry (HPLC–MS/MS) has been a common technique to evaluate the relative degree of global DNA methylation through determining the genome-wide level of cytosine and 5-mC in DNA samples [224].…”
Section: Epigenetic Effects Of Ionizing Radiation In Zebrafishmentioning
confidence: 99%
“…Recently, Pereira et al showed that γ irradiation increased the global methylation in both irradiated and bystander embryonic zebrafish fibroblast (ZF4) cells through mass spectrometry analyses [223]. High performance liquid chromatography–tandem mass spectrometry (HPLC–MS/MS) has been a common technique to evaluate the relative degree of global DNA methylation through determining the genome-wide level of cytosine and 5-mC in DNA samples [224].…”
Section: Epigenetic Effects Of Ionizing Radiation In Zebrafishmentioning
confidence: 99%
“…An analysis of the secretome of zebrafish embryonic cells showed no specific bystander proteins following low-doses irradiation with chronic X-rays [57]. The factors secreted by a human skin model were analysed following irradiation using a multidimensional LC-MS strategy [58].…”
Section: Ms-based Proteomic Studies Of Ribementioning
confidence: 99%
“…cytokines and other molecules) by the irradiated cells, contributing to the upregulation of oxidative metabolism in the bystander cells. [37][38][39][40] Interestingly, RIBE have been observed in a plethora of biological endpoints including DNA damage induction, [41][42][43][44] micronucleation, 45,46 genomic instability, 20,47,48 alteration in the microRNA (miRNA)…”
Section: Introductionmentioning
confidence: 99%
“…One approach is the transfer of medium from cultured irradiated cells to non-irradiated cells. 20,44,49,67 This technique allows simultaneously the detection and analysis of secreted RIBE factors in the conditioned medium and the study of their effect on non-irradiated (bystander) cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation